Inflammatory Stroma of Lymphoepithelioma-like Carcinoma of the Cervix: Immunohistochemical Study of 3 Cases and Review of the Literature. (September 2018) - Philippe, Amandine; Rassy, Marc; Craciun, Ligia; Naveaux, Céline; Willard-Gallo, Karen; Larsimont, Denis; Veys, Isabelle
Abstract : The aim of this study was to characterize the inflammatory infiltrate of the lymphoepithelioma-like carcinoma, a variant of squamous cell carcinoma clinically associated with a good prognosis. Immunohistochemistry was used to characterize 3 cases of lymphoepithelioma-like carcinoma in the uterine cervix, diagnosed over a period of 3 yr. The patients were between 30 and 50 yr old. Their cervical smears had shown atypical squamous cells of unknown significance or high-grade squamous intraepithelial lesions, and the initial cervical biopsy showed high-grade cervical intraepithelial neoplasia (CIN3) or squamous cell carcinoma. All patients underwent a Wertheim operation, 2 of which were preceded by a cervicectomy. Microscopically, all tumors were characterized by poorly defined sheets of undifferentiated squamous cells with a syncytial pattern and a dense background of infiltrating lymphocytes. Immunohistochemical analysis revealed that the lymphocytes were predominantly CD3 + and CD8 + T cells. The tumor lobules contained isolated CD8 + T cells, whereas CD4 + T cells and CD20 + B cells surrounded the tumor lobules. CD56 + NK cells and CD79 + B cells were scattered in the tumor tissue. An in situ hybridization staining for Epstein-Barr encoding region was negative but all cases were immunohistochemically positive for P16. Follow-up varied between 2 mo and 2.7 yr. All 3 patients were disease free. Lymphoepithelioma-like carcinoma of the uterine cervix is a variant of squamous cell carcinoma, known for its better prognosis. The good prognosis of this tumor is potentially explained by the high levels of infiltrating CD8 + T cells.